Evidence Synthesis in Harm Assessment of Medicines Using the Example of Rosiglitazone and Myocardial Infarction - Rietbergen, Charlotte; Stefansdottir, Gudrun; Leufkens, Hubert G.; Knol, Mirjam J.; De Bruin, Marie L.; Klugkist, Irene (Frontiers in Medicine, 2018)
The current system of benefit-risk assessment of medicines has been criticized for relying on intuitive expert judgment. There is a call for more quantitative approaches and transparency in decision making. Illustrated with the case of cardiovascular safety concerns for rosiglitazone we aimed to explore a structured procedure for the collection, quality assessment and statistical modelling of safety data from observational and randomized studies. We distinguished five stages in the synthesis process. In Stage I the general research question, population and outcome and general inclusion and exclusion criteria are defined and a systematic search is performed. Stage II focusses on the identification of sub-questions examined in the included studies and the classification of the studies into the different categories of sub-questions. In Stage III the quality of the identified studies is assessed. Coding and data extraction are performed in Stage IV. Finally, meta-analyses on the study results per sub-question are performed in Stage V. A Pubmed search identified 30 randomized and 14 observational studies meeting our search criteria. From these studies, we identified 4 higher level sub-questions and 4 lower level sub-questions. We were able to categorize 29 individual treatment comparisons into one or more of the sub-question categories, and selected study duration as an important covariate. We extracted covariate, outcome and sample size information at the treatment arm level of the studies. We extracted absolute numbers of myocardial infarctions from the randomized study, and adjusted risk estimates with 95% confidence intervals from the observational studies. Overall, few events were observed in the randomized studies which were frequently of relatively short duration. The large observational studies provided more information since these were often of longer duration. A Bayesian random effects meta-analysis on these data showed no ‘significant’ increase in risk of rosiglitazone for any of the sub-questions. The proposed procedure can be of additional value for drug safety assessment because it provides a stepwise approach that guides the decision making in increasing process transparency. The procedure allows for the inclusion of results from both randomized an observational studies, which is especially relevant for this type of research.